Manliga mönster och mönstermän: Maskulinitetskonstruktioner i och kring "Piteåuppropet" - Tenevall, Robert (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
This article raises the question why large numbers of men joined, or showed their support, for a male network against men's violence against women in the northern Swedish town of Piteå. The network, "Piteåuppropet", managed to raise a big sum of money for the local women's shelter, father hundreds of men for various rallies and gained a lot of media attention, locally, nationally and even internationally. The theoretical framework for the article can be found in the works of two radical thinkers, R. W. Connell and Slajov Žižek. R. W. Connell's concept of hegemonic masculinity is read with an understanding of hegemony influences by post-structuralist thinkers. This is done to understand how hegemonic masculinity can take on multiple forms in different groups of men. Slajov Žižek's understanding of Lacan's symptom is used to understand why the image of the "violent man" is needed to maintain the image of the "good" or "normal man". The main purpose with the network weemed to be breaking male silence on violence. However, other forms of male dominance remained unquestioned by "Piteåuppropet", hence maintaining the image of the "violent man" as invariably other.